2007
DOI: 10.3748/wjg.13.6109
|View full text |Cite
|
Sign up to set email alerts
|

Malakoplakia of the colon associated with colonic adenocarcinoma diagnosed in colonic biopsies

Abstract: Malakoplakia, typically involving the urinary tract, is an uncommon form of chronic inflammation caused by chronic infections and characterized by accumulation of macrophages. It has also been found in many other sites such as the gastrointestinal tract, pancreas, liver, lymph nodes, skin, respiratory tract, adrenal gland, vagina and brain. We present a case of a 64-year-old man referred to our hospital with cachexia and radiologic evidence of metastatic tumor of the liver. Colonoscopy revealed a large maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Although malakoplakia usually mimics malignancy, less than 30 cases of malakoplakia in association with adenocarcinoma of colon and rectum have been reported in English literature so far (9-12). Previous reports noted the possibility of over-estimating the pre-operative clinical stage of the disease, which can result in unsuitable treatment of the patients (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although malakoplakia usually mimics malignancy, less than 30 cases of malakoplakia in association with adenocarcinoma of colon and rectum have been reported in English literature so far (9-12). Previous reports noted the possibility of over-estimating the pre-operative clinical stage of the disease, which can result in unsuitable treatment of the patients (9).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that malakoplakia is usually found at the infiltrating border of the tumor without admixture with the neoplastic glands (11). Karasavvidou et al (12) reported a 64-year-old male patient with cachexia and radiological evidence of metastatic tumor of the liver. In colonoscopy a large malignant polypoid mass was identified in the colon along with multiple distinct polyps throughout the rest of the colon, which was in line with the findings of our reported case.…”
Section: Discussionmentioning
confidence: 99%
“…However, several pathogenic mechanisms have been proposed, such as infection, immunosuppression (immune deficiency disorders and organ transplantation), systemic illness, neoplasia, and genetic disorder. Intriguingly, most of the cases reported have shown an association between systemic diseases and colorectal adenocarcinoma [2, 7, 8, 9]. …”
Section: Discussionmentioning
confidence: 99%
“…Malakoplakia is notorious for mimicking a malignant neoplastic process. In fact, in a great majority of cases, the diagnosis first comes to light when a resection has been undertaken for the “malignant neoplasm.” Conversely malakoplakias have been reported to occur in association with adenocarcinomas including those of the colon and prostate [ 9 12 ]. Malakoplakia can pose significant challenges in staging of tumors as overstaging due to an overestimation of the size of the tumor may occur.…”
Section: Discussionmentioning
confidence: 99%